2020
DOI: 10.1038/s41436-020-0845-y
|View full text |Cite
|
Sign up to set email alerts
|

Automated syndrome diagnosis by three-dimensional facial imaging

Abstract: Purpose Deep phenotyping is an emerging trend in precision medicine for genetic disease. The shape of the face is affected in 30–40% of known genetic syndromes. Here, we determine whether syndromes can be diagnosed from 3D images of human faces. Methods We analyzed variation in three-dimensional (3D) facial images of 7057 subjects: 3327 with 396 different syndromes, 727 of their relatives, and 3003 unrelated, unaffected subjects. We developed and tested machine learning and parametric approaches to automated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 36 publications
1
61
0
1
Order By: Relevance
“…The team developed and tested various parametric and machine-learning approaches to automated syndrome diagnosis (Bannister et al, 2017(Bannister et al, , 2020, and applied these methods to compare their utility to automated diagnosis of syndromes with craniofacial dysmorphology. The best results came from the machine-learning approach, achieving balanced accuracy of 78.1% and sensitivity of 56.9% for syndrome diagnosis (Hallgrimsson et al, 2020). These studies demonstrated that facial deep phenotyping by quantitative facial 3D imaging has strong potential to be useful in clinical diagnosis.…”
Section: Facebase 2 Spoke Projectsmentioning
confidence: 88%
“…The team developed and tested various parametric and machine-learning approaches to automated syndrome diagnosis (Bannister et al, 2017(Bannister et al, , 2020, and applied these methods to compare their utility to automated diagnosis of syndromes with craniofacial dysmorphology. The best results came from the machine-learning approach, achieving balanced accuracy of 78.1% and sensitivity of 56.9% for syndrome diagnosis (Hallgrimsson et al, 2020). These studies demonstrated that facial deep phenotyping by quantitative facial 3D imaging has strong potential to be useful in clinical diagnosis.…”
Section: Facebase 2 Spoke Projectsmentioning
confidence: 88%
“…This method simplifies the use of HMR for 3D facial shape analysis that enables clinical diagnostic applications for many syndromes with associated facial dysmorphologies [3].…”
Section: Discussionmentioning
confidence: 99%
“…The proposed method was developed and evaluated using 185 HMR obtained at the Hospital Sant Joan de Déu in a 1.5T GE Sigma scanner. High-resolution structural 3D T1 MRI were obtained with the following acquisition parameters: matrix size 512×512; 180 contiguous axial slices; voxel resolution 0.47×0.47×1 mm 3 ; echo (TE), repetition (TR) and inversion (TI) times, (TE/TR/TI)=3.93ms/ 2000ms/ 710ms, respectively; flip angle 15. The stacked sets of images were loaded to the 3D analysis software for scientific data Amira (http://www.fei.com/software/amira-3d-for-life-sciences/) to manually reconstruct the 3D surfaces of the anatomy of the participants.…”
Section: Data Collection and Pre-processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative approaches, such as our approach here, have shown that craniofacial morphology is highly integrated. This applies to the constellations of features that characterize craniofacial anomalies and facial shape effects of major mutations but also to standing variation within naturally occurring populations (Hallgrímsson et al, 2009(Hallgrímsson et al, , 2020Martinez-Abadias et al, 2012;Cole et al, 2017). This is important because these patterns of covariation reveal underlying regularities in the relationship between developmental mechanisms and phenotypic variation.…”
Section: Wnt Signaling In Craniofacial Development and The Palimpsestmentioning
confidence: 99%